PROSPEK INDUSTRI KAIN TENUN MELAYU SIAK DI KABUPATEN SIAK SRI INDRAPURA - Said Muhammad Fadhli; Azwar Harahap; Syapsan ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in Siak Sri Indrapura Against weaving Malay entrepreneurs. This study aims to determine the industry's prospects wither siak woven fabric that will come in Siak Sri Indrapura. The population in this study amounted to 21 businesses using census method. The data used is derived from primary and secondary data obtained from the Department of Industry, Trade, Cooperatives and SMEs Siak Sri Indrapura, the Central Statistics Agency of Riau Province and the Central Agency of Statistics Siak Sri Indrapura.From the results of this study From the calculation that is used is the value of the Net Present Value (NPV), Benefit Cost Ratio (B / C), Net Benefit Cost Ratio (Net B / C), and Internal Rate Of Return (IRR). It is known that by using the Net Present Value (NPV) NPV values obtained siak Malay weaving industry in Siak Sri Indrapura Rp.11.163.133, - so that according to the criteria of Net Present Value (NPV) should be developed and has a great advantage.Keywords: Weaving melayu, Prospects, Small Industry, Labor, and Income.